Perbandingan Kebijakan Dana Komite Dengan Bantuan Operasional Sekolah Terhadap Peningkatan Profesionalisme Guru Di Sekolah Menengah Pertama Negeri 1 Pancarijang Pada Proses Pembelajaran - Febri Handika (JIA: Jurnal Ilmiah Administrasi, 2012)
Abstract Public policy is the government's action to deal with the problem, by directing people's attention to "who gets what, when, and how". While human resources' profesionalism is the ability and effort of a person to accomplish the job intensively. This research has been done at SMPN 1 Pancarijang, a type of descriptive-qualitative with population amount of forty-two (42) people, all accounted as sample, using survey, questionaire, interview, and literature study research methods. The data analysis method is quantitative using qualitative data. The result shows that whether there's an increased profesionality level or not after the School's Operational Funding policy being applied, indeed there is an increase of 47,6%. Also when we compare the Committee Funding with School's Operational Funding policy, we see 44,8% increase in teacher's profesionality on students' learning activity here at SMPN 1 Pancarijang.